The lived experience of frontline nurses: COVID‐19 in rural America. Issue 4 (20th April 2022) - Robinson, Karen R.; Jensen, Gwenneth A.; Gierach, Michelle; McClellan, Coreen; Wolles, Brenda; Bartelt, Samantha; Hodge, Janel
Abstract: Aim: This multisite study describes the lived experience of registered nurses (RNs) caring for coronavirus (COVID‐19) patients during the pandemic in rural America. Design: A qualitative phenomenological design was used. Methods: From January to June 2021, using the purposeful sampling method, 19 frontline nurses were interviewed regarding their experience caring for seriously ill COVID‐19 patients in three Upper Midwest tertiary care hospitals. Three doctoral prepared nurses transcribed and analyzed verbatim interviews with data interpreted separately and conjointly. Approved qualitative methods specific to transcendental phenomenology were used. Results: This phenomenological study identified four themes describing the lived experience: (1) feeling of being overwhelmed, (2) feeling of role frustration related to chaos in the care environment, (3) feeling of abandonment by leaders, families, and communities, and (4) progressing from perseverance to resilience. Implications for Practice: Significant implications include ensuring frontline RNs are in communication with leaders, and are involved in tactical planning. Leaders can provide a stabilizing presence, build resilience, confidence, and security. Recommendations for additional research are provided. Conclusion: Nurses in intensive care and COVID‐19 designated medical units had experiences similar to high population United States and international cities. Their shared experience included high volumes of critically ill patients in hospitals frenzied by rapid change, uncertainty, and capacity strain. Differences in the experience of rural nurses included close social connection to patients, families, and community members. This rural connectedness had both positive and negative effects.